Exploring Aluminum Tolerance at Seedling Stage in Rice (Oryza sativa, Linn) by Using Modified Magnavaca Nutrient Solution - Nurul Hidayatun; Maria Genaleen Q. Diaz; Abdelbaghi M. Ismail (Buletin Plasma Nutfah, 2017)
Aluminum (Al) toxicity is considered as one of the main constraints for crop production in acidic soil. This study was subjected to observe the response of root and shoot growth of eight rice varieties under Al stress in hydrophonic solution. A modified Magnavaca’s solution was used to compare the effect of Al stress using different variables which were relative root elongation (RRE), relative shoot length (RSL) and relative root weight (RRW). The experiment was conducted in split-plot experimental design. Eight rice varieties were screened in four Al levels (0 μM, 540 μM, 750 μM, and 1,300 μM). Root length, shoot length,and root dry weight were measured after 7 days of treatment, then the RRE, RSL, and RRW were calculated. The results showed that Al significantly reduced RRE and RSL but increased RRW. RSL was reduced as the Al concentration increased while RRE reduction started only at 750 μM Al concentration. It was observed that RRW was significantly higher under 540 and 750 μM Al concentration. However, no significant difference was observed in 1,300 μM Al concentration. The increase in root weight is partly attributed by the thickening of the root wall, but this effect was diminished due to root hair inhibition under 1,300 μM Al concentration. Among these three variables observed, root and shoot lengths indicated better variables in determining Al tolerance in rice, compared to root weight. However, these variables were not sufficient to represent root and shoot growth inhibition, and not sufficient to be used solely for Al toxicity screening